Utilization of virtual and digital technologies in reducing psychological problems in the elderly with chronic illness: A systematic review - Indira Mastura Pulungan; Etty Rekawati; Dikha Ayu Kurnia; Utami Rachmawati (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Globally the prevalence of chronic diseases continues to increase every year. In 2021, it is estimated that around 43 million people will die from chronic diseases, with 73% of them being prevalent in low-income or developing countries. Purpose: To conduct an analysis related to the use of virtual and digital technology in reducing psychological problems in the elderly with chronic diseases. Method: This paper is a review of the literature related to the topic of the use of virtual and digital technology in the elderly with chronic diseases on its effect on psychological problems. The analysis begins with a literature search across several databases, including PubMed, Google Scholar, Sage Journals, ProQuest, ScienceDirect, and SpringerLink. The article search was conducted using the PICO form (P = Elderly with chronic diseases; (2) Intervention = Utilization of virtual technology, utilization of digital technology; (3) Outcomes = Reducing psychological problems, elderly rehabilitation). The author identified 33 articles for analysis and filtered them, resulting in 5 articles that employed the Randomized Controlled Trial (RCT) research method. Furthermore, the author conducted an analysis using a critical appraisal form, namely the CASP (Critical Appraisal Skill Program) form. Results: The virtual technologies can minimise depression, anxiety, and increase self-efficacy in elderly people with chronic disease. The digital application technologies give a psychological impact based on the features and the basic purpose of making that application. Conclusion: Virtual and digital technologies have an impact on the psychological well-being of the elderly, based on the features that these technologies provide for them.